Phylogeny Best Explains Latitudinal Patterns of Xylem Tissue Fractions for Woody Angiosperm Species Across China - Zheng, Jingming; Zhao, Xia; Morris, Hugh; Jansen, Steven (Frontiers in Plant Science, 2019)
Investigating space allocation patterns of plant secondary xylem along a latitudinal gradient is useful to evaluate structure-function tradeoffs in woody angiosperm xylem. An anatomical dataset including 700 woody angiosperm species across China was compiled together with latitudinal and climate data for each species. The relative tissue fractions of vessels, fibers, and parenchyma (including ray and axial parenchyma) in xylem were analyzed to determine the effect of latitudinal differences and phylogeny on anatomical variation. The analyses revealed a trade-off between vessel and non-vessel fraction across latitude, with tissue fraction trade-offs mainly occurring between vessels and fibers, and between fibers and total parenchyma. Among 13 climate variables, thermal indices generally had greater explanatory power than moisture indices in bi-variate models for all cell types, while mean annual temperature, mean temperature of the coldest month, and annual actual evapotranspiration were included in the top multi-variate models explaining variance of different tissue fractions. Phylogeny and climate together explained 57 to 73% of the total variation in xylem space occupancy, with phylogeny alone accounting for over 50% of the variation. These results contribute to our knowledge of wood structure-function and are relevant to better understand forest response to climate change.